2017
DOI: 10.1111/fcp.12279
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of transient receptor potential vanilloid‐1 confers neuroprotection, reduces tumor necrosis factor‐alpha, and increases IL‐10 in a rat stroke model

Abstract: Stroke is a major cause of mortality and long-term disability in adults. Transient receptor potential vanilloid-1 (TRPV1) plays a crucial role in neuroinflammation. In this study, the effects of TRPV1 agonist (capsaicin) and antagonist (AMG9810) on cerebral ischemia were investigated. Forty male Wistar rats were assigned to the following experimental groups: sham, vehicle) ischemic), AMG9810 (selective TRPV1 antagonist, 0.5 mg/kg; 3 h after stroke), and capsaicin (1 mg/kg; 3 h after stroke). Stroke was induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…TRPV1 promotes activation of astrocytes and the release of astrocyte-derived IL-1β, predominantly via the Janus kinase 2-signal transducer and activator of transcription 3 signaling pathway, and activation of the nucleotide-binding oligomerization domain-like receptor protein 3 inflammasome in hypoxic-ischemic encephalopathy (44). Overall, these comprehensive analyses suggest that the expression of TRPV1 is closely associated with the inflammatory response and that regulation of TRPV1 may reduce the inflammation induced by ischemic injury (42).…”
Section: Trpv1 In Inflammationmentioning
confidence: 93%
See 1 more Smart Citation
“…TRPV1 promotes activation of astrocytes and the release of astrocyte-derived IL-1β, predominantly via the Janus kinase 2-signal transducer and activator of transcription 3 signaling pathway, and activation of the nucleotide-binding oligomerization domain-like receptor protein 3 inflammasome in hypoxic-ischemic encephalopathy (44). Overall, these comprehensive analyses suggest that the expression of TRPV1 is closely associated with the inflammatory response and that regulation of TRPV1 may reduce the inflammation induced by ischemic injury (42).…”
Section: Trpv1 In Inflammationmentioning
confidence: 93%
“…Preventing the inflammatory response is therefore another important approach that is essential for protecting the brain. A previous study demonstrated that TRPV1 inhibition decreased levels of TNF-α and IL-10 in plasma, which reduced infarction size, thus conferring a neuroprotective effect (42). Another study revealed that inhibiting TRPV1 exerted neuroprotection in rats with cerebral IR injury, which was partially associated with TRPV1-mediated antioxidant stress and anti-inflammation due to inhibiting p38 MAPK activation (43).…”
Section: Trpv1 In Inflammationmentioning
confidence: 98%
“…Brain swelling results from increased vascular leakage and disruption of the blood brain barrier [8, 9]. TRPV1 activation promotes vasodilation and oedema formation [53, 54]. Then, the contribution of TRPV1 to brain oedema formation was assessed in infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IFN γ and TNF α have been linked to cerebral malaria progression by acting on brain endothelial cells, thus promoting their activation and/or apoptosis [67, 68]. Recently, the TRPV1 antagonist AMG9810 was found to confer neuroprotection by attenuating TNF α production in a rodent model of stroke [54]. These evidences and the gathered data allow us to suggest that the diminished cytokine generation by TRPV1KO mice contributes to the diminished brain swelling and damage observed in P. berghei ANKA-infected mice, a response that is associated with a greater ability of these mice to produce higher amounts of oxygen/nitrogen-derived oxidant species which in turn may enhance their capacity of killing this parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is another reaction after cerebral ischemia, and the function of free radical scavenging system in the body decreased during cerebral ischemia. The endogenous antioxidant systems are unbalanced and produced large amounts of free radicals, leading to the peroxidation of lipid, protein and nucleic acid, and the biochemical alteration (SOD ↓, GSH-Px ↓, and MDA↑), and further led to BBB disruption with secondary vasogenic edema, activation of apoptosis, and brain infarction [47, 48]. Therefore, the production and release of oxygen free radicals are the key steps that cause cerebral injury.…”
Section: Discussionmentioning
confidence: 99%